Numerical Studies and Analyses on the Acidizing Process in Vug Carbonate Rocks - Jia, Cunqi; Sepehrnoori, Kamy; Zhang, Haiyang; Yao, Jun (Frontiers in Earth Science, 2021)
A vug porosity system, in addition to a matrix, is also the target rocks for the acidizing. In this work, the acidizing process in two typical core-scale separate-vug porosity systems is studied in detail. Numerous cases are conducted to discuss a parametric study on the acidizing process and hydraulic behavior. Results indicate that the presence of vug reduces the pore volume of acid solution consumed to achieve a breakthrough, which is consistent with experimental observations. Increasing the vug diameter and porosity decreases pore volume to breakthrough both for a vugular carbonate rock and isolated vug carbonate rock. In comparison, the acid mass does not change a lot. Typical dissolution patterns can also be observed in the acidizing process when a vug exists. Compared to matrix dissolution patterns, the presence of vug induces wormhole to pass through the vug region.